PERANCANGAN BOOKLET MELALUI MOTIF-MOTIF SONGKET PANDAI SIKEK - RISA PAMILA RAHMAH, Dr. Budiwirman, M.Pd. Hendra Afriwan, S.Sn., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2017)
Purpose of this final work is (1) Designing the booklet as a medium to deliver information motives songket (2) one of the country very well known with songketnya smooth and beautiful motives is clever Pandai Sikek. Then to document the motives clever Pandai Sikek. And also the promotion of cultural recognition is expected to mointain a visual language that is priciless.Keyword: Pandai Sikek, motives, booklet.